Youth, entrepreneurship, and tourism in peripheral areas - Savelli, Elisabetta; Travasi, Alessio; Pierli, Giada; Murmura, Federica (Piccola Impresa / Small Business, 2025)
Purpose. The present study analyses the role of young people in entrepreneurship and tourism in peripheral Italian areas, with a particular focus on the Marche region. The objective of the study is to understand the degree of attachment of young people to the territory, their perceptions of local resources, and the barriers that hinder their active involvement in the tourism and entrepreneurial development of these areas. Design/methodology/approach. The research is grounded in a quantitative survey conducted through a structured questionnaire, administered to a sample of 313 young individuals (aged 18-35) residing in the Basso Appennino Pesarese and Ancona area (ABPA). The analysis explores four key areas: development priorities, mobility models, community involvement, and the enhancement of the local tourism offer. Findings. The results of the study demonstrate the pivotal function of tourism and services in the economic development of peripheral regions. There is a notable interest among young people in the advancement of these areas. Nevertheless, the analysis reveals critical concerns pertaining to mobility, inadequate infrastructure, and a paucity of cultural events and networking prospects. The aspiration to reside in these areas is frequently impeded by the perception of limited employment and business prospects. Practical and Social implications. The study provides valuable indications for the formulation of public policies and the development of local strategies, suggesting actions to enhance infrastructure, promote youth entrepreneurship and integrate local communities and tourism. The strengthening of social networks and the active involvement of young people are identified as pivotal elements for the economic and social sustainability of peripheral regions. Originality of the study. The present paper makes a contribution to the ongoing debate on the development of peripheral areas. It achieves this by highlighting the active role of young people in the local economy, as demonstrated through tourism and entrepreneurship. The empirical analysis it presents offers novel perspectives for understanding territorial dynamics in marginal contexts.